(3GdLGeY TQM GdJMQjQs - (3CHh GdMSjf RjO Hf eMeOs; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3gPG eG ENJUQfG ef TQM cJGH GdJMQjQ , hChOYfGg ef hLhg eSGFdg hYjhfgG , eY RhGFO cKjQI s
(3BNQgG (B:s
(3aUd , bGd GdSjO e HGddg ai eSGaQ dGjecfg GdfRhd Yf GdOGjI ddWgGQI LGR Cf jJjee , heKdg ai GdhGai jJdhg HGH GdMjV s
(3GdLRA GdChd ef SJI YTQ LRAkGs
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
Keywords: (3abg GdePGgH GdCNQis